2014
DOI: 10.1021/jp408360j
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Processed Cu2ZnSnS4 Nanocrystal Solar Cells: Efficient Stripping of Surface Insulating Layers Using Alkylating Agents

Abstract: Solution-processed photovoltaic (PV) devices based on semiconductor nanocrystals (NCs) such as Cu 2 ZnSnS 4 (CZTS) and CuInS 2 (CIS) are attracting much attention for use in next-generation solar cells. However, the performance of NCbased devices is hindered by insulating surface-capping ligands that limit transfer/transport of charged carriers. Here, to remove surface-capping ligands (long-chain fatty amines) from NCs, we use the strong alkylating agent methyl iodide, which converts primary amines to quaterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 32 publications
0
39
0
Order By: Relevance
“…3. The nanostructures were copper-poor and zinc-rich at all x contents except for x = 1 (Suehiro et al, 2014;Fischereder et al, 2010;Jiang et al, 2011). This indicates a higher p-type conductivity, which can be useful for PV applications (Chen et al, 2010).…”
Section: Structural Propertiesmentioning
confidence: 88%
“…3. The nanostructures were copper-poor and zinc-rich at all x contents except for x = 1 (Suehiro et al, 2014;Fischereder et al, 2010;Jiang et al, 2011). This indicates a higher p-type conductivity, which can be useful for PV applications (Chen et al, 2010).…”
Section: Structural Propertiesmentioning
confidence: 88%
“…Previously, we demonstrated that ligand striping with alkylating agents such as methyl iodide and the Meerwein's reagent is effective in producing CZTS NC‐based solar cells without heat treatments at higher temperatures . The use of alkylating agents allowed for the removal of capping agents at moderate conditions such as lower temperatures, which is very important for some applications where NC layers should be used without high temperature annealing.…”
Section: Introductionmentioning
confidence: 99%
“…They also developed all‐semiconductor NC solar cells with CdSe (n‐type) and CdTe (p‐type) NCs 2. So far, a variety of semiconductor NCs, such as CdTe,3, 4 PbS x Se 1− x ,5, 6 Cu 2 S,7 CuInSe 2 ,8, 9 and Cu 2 ZnSnS 4 ,10, 11 have been used for such NC‐based solar cells. These cells rely on the carrier transfer between n‐ and p‐type NCs.…”
Section: Introductionmentioning
confidence: 99%